(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
This article examines the issues of improving the socio-psychological management system of higher education institutions. The processes of selecting, training, and improving the qualifications of managerial personnel are analyzed based on empirical research. The role of motivation, psychological adaptation, and emotional intelligence in enhancing the efficiency of the management system is emphasized. The possibilities of supporting the professional development of managers and teaching staff by improving the quality of psychological services in educational institutions are considered.